230k views
4 votes
Given
f(x)= 4x^2 + 6x and g(x) = 2x^2 +13x+15 \\, find (f/x) (x)

2 Answers

3 votes

ANSWER


( (f)/(g) )(x) = (2x )/(x + 5)

where


x \\e - (3)/(2) \: or \: x = - 5

EXPLANATION

The given functions are:


f(x) = 4 {x}^(2) + 6x

and


g(x) =2 {x}^(2) + 13x + 15

We want to find ,


( (f)/(g) )(x) = (f(x))/(g(x))


( (f)/(g) )(x) = \frac{4 {x}^(2) + 6x }{2 {x}^(2) + 13x + 15}


( (f)/(g) )(x) = \frac{2x(2x + 3) }{2{x}^(2) + 10x +3x + 15}


( (f)/(g) )(x) = \frac{2x(2x + 3) }{2{x}(x + 5) +3(x + 5)}


( (f)/(g) )(x) = (2x(2x + 3) )/((2x + 3)(x + 5))

We cancel out the common factors to get:


( (f)/(g) )(x) = (2x )/(x + 5)

where


x \\e - (3)/(2) \: or \: x = - 5

User Zhun Chen
by
5.9k points
3 votes

Answer:
(f/g)(x)=(2x)/(x+5)

Explanation:

Given the function f(x):


f(x)=4x^2+6x

And the function g(x):


g(x)=2x^2+13x+15

To find
(f/g)(x) you need to divide the function f(x) by the function g(x).

Therefore, knowing this, you get:


(f/g)(x)=(4x^2+6x)/(2x^2+13x+15)

You can simplify the numerator by factoring out 2x:


(f/g)(x)=(2x(2x+3))/(2x^2+13x+15)

You have to simplify the denominator:

Rewrite the term 13x as a sum of two terms whose product be 30:


(f/g)(x)=(2x(2x+3))/(2x^2+(10+ 3)x+15)

Apply Distributive property:


(f/g)(x)=(2x(2x+3))/(2x^2+10x+ 3x+15)

Make two groups of two terms:


(f/g)(x)=(2x(2x+3))/((2x^2+10x)+ (3x+15))

Factor out 2x from the first group and 3 from the second group:


(f/g)(x)=(2x(2x+3))/((2x(x+5))+ 3(x+5))

Factor out (x+5):


(f/g)(x)=(2x(2x+3))/((2x+3)(x+5))

Simplifying, you get:


(f/g)(x)=(2x)/(x+5)

User Cherry Vanc
by
5.0k points